Diagnosis and Management of Catheter Associated Urinary Tract Infection - Muhammad Rizwan, Mohsina Hamid, Muhammad Saleh Khaskheli, Munazzah Meraj, Naheed Akhtar (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Catheter associated Urinary Tract Infection (CAUTI ) is predominant type of Hospital acquired infection causing antimicrobial resistance. The main objective for it to elaborate those points which cause catheter associated urinary tract infection. The main program features were dissemination of information to sponsor organizations and hospitals, data collection, and guidance on key technical and socio-adaptive factors in the prevention of catheter-associated UTI. As the management and prevention of catheter associated urinary tract infections have become a priority and challenge for most of hospitals. So, the present review article is prepared to provide information about the CAUT’S Infection. Management involve, aseptic insertion of catheter, prevent longer catheterization, and timely removal of catheter. Staff training and education related to catheterizations play a major role to manage CAUTIs. Uses of intermittent, condom catheter, antimicrobial catheter, limiting the placement or alternative of catheterization base on specific indications are significance to prevent CAUTIs.